Black Feminist Hip-Hop Rhetorics and the Digital Public Sphere. Issue 2 (3rd April 2017) - Duthely, Regina
Abstract: Digital public discourse spaces like Twitter and blogs like The Crunk Feminist Collective allow for Black voices not only to be inserted in the mainstream media, but to transform those media to focus on their needs from their perspective. These digital counterdiscourses challenge the traditional boundaries between the academy and the community, and invite students and scholars to consider the real-world uses of writing and technology and its ability to change the world.